Racial Disparity in U.S. Imprisonment Across States and Over Time - Enders, Walter (Journal of quantitative criminology, 2019)
We analyze the contribution of changes in the black-white racial disparity in imprisonment to changes in the black incarceration rate. We also describe the behavior of the racial disparity across states and across time.